ANALYTICAL MODEL OF HEXAGONAL WIRE MESH REINFORCEMENT WITH WEATHERED BANGKOK CLAY BACKFILL - D. T. Bergado; P. Voottipruex; A. Asanprakit; C. Teerawattanasuk (International Association of Lowland Technology, 2001)
An analytical method is proposed for determining the pullout resistance/pullout displacement relationship for both of PVC-coated and zinc-coated hexagonal wire mesh reinforcement. The parameters used in this analytical model were obtained from pullout testing programs, such as shear stiffness (ks) and initial slope of pullout bearing resistance (Eip). In addition, this method can predict the movement characteristics of both PVC-coated and zinc-coated hexagonal mesh during pullout. The displacements along the reinforcement axial stiffness and the friction resistance can be simulated by linear, elastic-perfectly plastic model. The hyperbolic model can be used to calculate the bearing resistance. Reasonable agreement between the predicted and measured pullout resistances were obtained. From the predicted values, the percentages of the friction resistances to the total pullout resistances are 18% and 16% for zinc-coated and PVC-coated wire mesh, respectively. Consequently, the bearing resistances are 82% and 84% of the total pullout resistances for zinc-coated and PVC-coated hexagonal wires,respectively. The ratios of friction resistances are 22% and 19% for the zinc-coated and the PVC-coated wire meshes, respectively. The total pullout resistances in the zinc-coated mesh is higher than PVC-coated mesh by approximately 20%. Furthermore, the weathered clay backfill was found to have higher pullout resitance and lower pullout displacement than the silty sand backfill.